Messengers of Human Security: Malala Yousafzai and Immaculée Ilibagiza - Repez, Filofteia; Iftode, Florin (Acta Universitatis Danubius. Relationes Internationales, 2023)
Human security is a people-centered approach that has gained considerable attention on the diplomatic and political agenda. Ensuring and maintaining human security is conditioned by respect for human rights and human dignity. Over time, a series of theoretical and practical contributions in support of human security can be noted. The article aims, after a brief presentation of the concept of human security, to highlight the effort and courage of two messengers of human security from different countries and continents - Malala Yousafzai and Immaculée Ilibagiza.